Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1399-0012.2012.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan in heart transplantation candidates with severe pulmonary hypertension: efficacy, safety and outcome after transplantation

Abstract: In patients considered high-risk candidates for heart transplantation because of high PVR, therapy with bosentan is associated with a significant reduction in PVR and a good outcome after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…This is in agreement with previous reports on the beneficial effect of bosentan therapy on PVR and diastolic pulmonary pressure, which enabled a subset of responders to bosentan to become eligible for heart transplantation [7, 11]. After bosentan titration, PVR decreased by 60% compared with baseline values at the 12-month follow-up in heart transplant candidates with severe PH [12]. The reduction in PVR with bosentan therapy is associated with favorable outcome after transplantation and LV assist device implantation [12, 13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with previous reports on the beneficial effect of bosentan therapy on PVR and diastolic pulmonary pressure, which enabled a subset of responders to bosentan to become eligible for heart transplantation [7, 11]. After bosentan titration, PVR decreased by 60% compared with baseline values at the 12-month follow-up in heart transplant candidates with severe PH [12]. The reduction in PVR with bosentan therapy is associated with favorable outcome after transplantation and LV assist device implantation [12, 13].…”
Section: Discussionsupporting
confidence: 91%
“…After bosentan titration, PVR decreased by 60% compared with baseline values at the 12-month follow-up in heart transplant candidates with severe PH [12]. The reduction in PVR with bosentan therapy is associated with favorable outcome after transplantation and LV assist device implantation [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Though modest in extent, the clinical behavior post‐OHT was dramatic and more akin to pre‐capillary PH physiology characterized by PH crisis and death. Though small studies in non‐CHD OHT recipients treated with PH‐directed therapy pre‐transplant show promising results with good survival, reversal of PH, and good functional capacity in survivors, larger studies are lacking, especially in CHD. These two patients alone exemplify the need to better understand the nature and treatment of PAH in CHD.…”
Section: Discussionmentioning
confidence: 99%
“…, Perez‐Villa et al . ). Hefke and colleagues reported that bosentan was an independent predictor of reduced mortality in a group of 84 patients on the waiting list for heart transplantation (Hefke et al .…”
Section: The Treatment Of Ph Due To Lhfmentioning
confidence: 97%
“…reported that 12 months of bosentan therapy reversed previously defined irreversible PVR in 19 of 26 patients, making them eligible for heart transplantation (Perez‐Villa et al . ). They also observed that one‐year survival among the 14 patients who underwent heart transplantation was similar to that in the 56 patients who did not have increased PVR prior to heart transplantation (Perez‐Villa et al .…”
Section: The Treatment Of Ph Due To Lhfmentioning
confidence: 97%